Impact of debt relief on investment - MASHODO, Frank (KDI School, 2015)
As of September 2014, 35 countries have benefited under the Heavily Indebted Poor Countries (HIPC) Initiative as the program is near completion, of which 29 are in Sub-Saharan Africa with a total spending of around US$75 billion. This paper measure the impact of debt relief under the HIPC Initiative on investment (total, private and public) in SSA within the framework of the debt overhang hypothesis and the fiscal space theory. The Difference in Difference model was applied on a panel data of 15 countries, only 8 countries that received debt relief from 2003 to 2005 and 7 non-HIPC covering the period 1996 to 2013 to access the impact of HIPC Initiative in SSA on total, private and public investment. The results indicated that HIPC Initiative had significant impact on total investment in the region. This increase in total investment in SSA was mainly driven by private investment, which proved to have highly responded positively to debt relief owing to improved macroeconomic stability brought by the implementation of set conditionalities. However, there was little evidence to support the claim the HIPC Initiative has significant impact of public investment. In this regard, the results supported the debt overhang hypothesis in SSA and found little evidence for the fiscal space theory. This paper, therefore, concluded that debt relief affects investment in SSA by; 1) eliminating the debt overhang and encouraging investment and then growth, and 2) improving institutional and governance quality of beneficiary countries that will adopt specific reform programs and in turn encourage private investment.
Thesis(Master) --KDI School:Master of Public Policy,2015